A Novel Direct Torque Control Permanent Magnet Synchronous Motor Drive used in Electrical Vehicle - Yaohua Li; Ma Jian; Yu Qiang; Liu Jiangyu (Institute of Advanced Engineering and Science, 2011)
In this paper, a modified direct torque control (DTC) scheme for permanent magnet synchronous motor (PMSM) is investigated, which enables low torque ripple by using an improved voltage vector selection strategy instead of switching table used in conventional DTC. Based on the control of stator flux, torque angle and torque, voltage vector selection strategy of PMSM DTC drive is proposed. In the proposed voltage vector selection strategy, the applied voltage vector is determined according to outputs of hysteresis comparators for stator flux and torque, angular position of stator flux and torque angle, which is finally synthesized by space vector modulation (SVM). Modeling and experimental results for an interior PMSM used in Honda Civic 06My Hybrid electrical vehicle are given. Simulation and experimental results show torque ripple is reduced and the total harmonics of stator current is decreased when compared those of conventional DTC. And a fixed switching frequency is obtained with the help of SVM. In addition, the proposed DTC doesn’t need any additional PI controller, which maintains the simplicity in conventional DTC.DOI: http://dx.doi.org/10.11591/ijpeds.v1i2.141Keywords: direct torque control, permanent magnet synchronous motor, electrical vehicle, torque ripple, switching frequency